Is Hemoglobin Mass at Age 16 a Predictor for National Team Membership at Age 25 in Cross-Country Skiers and Triathletes? - Wehrlin, Jon Peter; Steiner, Thomas (Frontiers in Sports and Active Living, 2021)
We recently measured the development of hemoglobin mass (Hbmass) in 10 Swiss national team endurance athletes between ages 16–19. Level of Hbmass at age 16 was an important predictor for Hbmass and endurance performance at age 19. The aim was to determine how many of these young athletes were still members of Swiss national teams (NT) at age 25, how many already terminated their career (TC), and whether Hbmass at ages 16 and 19 was different between the NT and TC group. We measured Hbmass using the optimized carbon monoxide re-breathing technique in 10 high-performing endurance athletes every 0.5 years beginning at age 16 and ending at age 19. At age 25, two athletes were in the NT group and eight athletes in the TC group. Mean absolute, body weight-, and lean body mass (LBM) related Hbmass at age 16 was 833 ± 61 g, 13.7 ± 0.2 g/kg and 14.2 ± 0.2 g/kg LBM in the NT group and 742 ± 83 g, 12.2 ± 0.7 g/kg and 12.8 ± 0.8 g/kg LBM in the TC group. At age 19, Hbmass was 1,042 ± 89 g, 14.6 ± 0.2 g/kg and 15.4 ± 0.2 g/kg LBM in the NT group and 863 ± 109 g, 12.7 ± 1.1 g/kg and 13.5 ± 1.1 g/kg LBM in the TC group. Body weight- and LBM related Hbmass were higher in the NT group than in the TC group at ages 16 and 19 (p < 0.05). These results indicate, that Hbmass at ages 16 and 19 possibly could be an important predictor for later national team membership in endurance disciplines.